Financial Management Practices in SMEs: Challenges and Solutions - Ela Widasari; Paniran Paniran; Furniawan Furniawan; Firda Mufidah (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Small and medium-sized enterprises (SMEs) are essential to economic growth and job creation but face unique financial management challenges that can impede their sustainability and growth. Limited access to capital, insufficient financial planning, and inadequate accounting skills are among the main obstacles hindering SMEs' financial success. Purpose. This study aims to identify the primary challenges in financial management practices among SMEs and to propose solutions that can enhance their financial stability and growth potential. Method. A mixed-methods approach was used in this research, combining quantitative data from SMEs' financial performance metrics with qualitative insights from interviews with SME owners and financial managers. Financial metrics provided an overview of common problem areas, while interviews gave a deeper understanding of the practical challenges SMEs encounter. Results. The findings indicate that SMEs commonly struggle with cash flow management, budgeting, and accessing credit, which undermines their operational efficiency and resilience. Additionally, limited financial literacy among SME managers further exacerbates these challenges, often leading to ineffective financial decision-making. Conclusion. The study concludes that targeted training in financial literacy, better access to funding options, and support for implementing accounting systems can significantly improve the financial health of SMEs. Policy implications suggest that collaboration between government bodies and financial institutions is crucial to develop tailored financial solutions, focusing on accessible financing and financial education. These strategies could empower SMEs to overcome financial challenges, strengthening the SME sector’s role in the economy.